Iron`s true weight: Does the amount of iron in the body equate to the amount of iron on the bar in Australian Football League women`s players? - Pengelly, M.; Pumpa, K. L.; Pyne, D. B.; Etxebarria, N. (Nutrients, 2025)
Background: The physiological requirements of a successful team sport performance partly depend on iron-facilitated mechanisms. However, how low iron stores affect team sport athletes remains unclear.